(3QSGdI JJYdb HGdCeQGV GdUOQjIs ((3oeUWai Hf edG eMeO GdHSfhj s)
(3ChdgG (B:s
(3hHYO agPg QSGdI JJYdb HGdCeQGV GdUOQjI eQJHI Ydi ebOeI hNeSI aUhd hNGJeI GdebOeI (B: (3GdHOf eQcH ef KdGKI CTjGA ef CYVGA UdHI s
(3BNQgG (B:s
(3hCTO GdfGS ESJZfGA Yf GdLeGY ef jUjHg YbHg cSd hPHhd faS ajfHZi Cf jLfH efg ef jYJQjg gPg GdYQGV , hjVQ HCUMGH GdCHOGf GdjGHSI aGYde Pdc hGddg CYde s
(3GfXQ eY GdJMaI GdLeYI deaQOGJ GdWH GdfGaYI Qbe (B"366"s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B101 s
Keywords: (3GdWHs